Respuesta :
Solving for F by rearranging the formula given will give us: [tex]\mathbf{F = \frac{9C}{5} + 32}[/tex]
Given the formula, [tex]C = \frac{5}{9} (F - 32)[/tex]
To rearrange the formula for F.
To do this, we are to make F the subject of the formula as follows:
[tex]C = \frac{5}{9} (F - 32)[/tex]
- Multiply both sides by [tex]\frac{9}{5}[/tex]
[tex]C \times \frac{9}{5} = \frac{5}{9} (F - 32) \times \frac{9}{5} \\\\\frac{9C}{5} = F - 32[/tex]
- Add 32 to both sides of the equation
[tex]\frac{9C}{5} + 32 = F - 32 + 32\\\\\frac{9C}{5} + 32 = F\\\\\mathbf{F = \frac{9C}{5} + 32}[/tex]
Therefore, solving for F in the formula given will give us: [tex]\mathbf{F = \frac{9C}{5} + 32}[/tex]
Learn more here:
https://brainly.com/question/21727387